The University of Michigan, Museum of Art : Annual Report 1998 - 1999. - Steward, James Christen; University of Michigan Museum of Art, Michigan (Michigan : University of Michigan, Museum of Art, 1999)
Dow, Jim ; Delacroix, Eugène ; Doisneau, Robert ; Steichen, Edward ; Atget, Eugène ; Newman, Arnold ; Seymour, Truma ; Jacobson, Bill ; et al.
Overzicht verschillende tentoonstellingen in 1998 - 1999.
kunstcatalogus